Briquetting and carbonization of naturally grown algae biomass for low-cost fuel and activated carbon production. (15th November 2017) - Amarasekara, A.; Tanzim, F.S.; Asmatulu, E.
Abstract: This study reports the briquetting and carbonization processes of naturally grown algae biomass collected from regional lakes. After drying them in air and chopping them into small pieces (∼2.5 × 2.5 cm), three different briquetting pressures (e.g., 2, 3, and 5 tons/cm 2 ) were applied to form algae briquettes with 3–5% moisture content. Three major investigations were performed on the prepared samples. The first test was to investigate the briquettes' handleability, in which the algae briquettes were dropped 100 times from a height of 1.524 m to resemble a handling mechanism. The second test was conducted on the samples to resolve the residual strength of the briquettes before and after the carbonization process at 800 °C. Ignition points of the algae briquettes were reviewed in the third analysis. Test results showed that briquettes under 2, 3, and 5 tons/cm 2 of pressure had density values of 1303, 1423, and 1553 kg/m 3, respectively. Drop tests demonstrated that the weight contractions of the briquettes were reduced from 10.2% to 2.1%, when the pressure was intensified from 2 to 5 tons. Ignition temperatures for the non-carbonized briquettes under 2, 3, and 5 tons/cm 2 were 492, 510, and 520 °C, respectively; however, after carbonization, these temperatures were reduced to 474, 487, and 492 °C, respectively. Compression strength tests for the non-carbonized briquettes under 2, 3, and 5 tons/cm 2 resulted in 22.1, 29.2, and 33.5 MPa, respectively. These test outcomes can be suitable for future guidance of an algae-based biomass and fuel system for reducing environmental impacts.